Charge transfer time in alkanethiolate self-assembled monolayers via resonant Auger electron spectroscopy - Kao, Ping; Neppl, Stefan; Feulner, Peter; Allara, David L.; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
The dynamics of the charge transfer (CT) in alkanethiolate self-assembled monolayers is addressed by resonant Auger spectroscopy using the core hole clock method. The CT pathway was unambiguously defined by resonant excitation of the nitrile tailgroup attached to the alkyl backbone. The length of this backbone was varied to monitor the respective dependence of the CT time. It was found that, similar to the static conductance, this dependence can be coarsely described by an exponential function with an attenuation factor of 0.93 per methylene unit (0.72 Å−1; a tunneling along the chain was assumed). As a result, the CT time is quite long even for a relatively short alkyl chain; in particular, it is ca. 100 fs for the chain consisting of only four CH2 units. In contrast, the CT time associated with the thiolate headgroup anchor was found to be quite short, viz. 2.3 fs, which suggests an efficient interfacial electronic coupling between the aliphatic backbone of the CnCN molecules and the substrate over the thiolate−gold linkage.
Gesehen am 01.03.2023